Reconstruction and optimization of a Pseudomonas putida-Escherichia coli microbial consortium for mcl-PHA production from lignocellulosic biomass - Qin, Ruolin; Zhu, Yinzhuang; Ai, Mingmei; Jia, Xiaoqiang (Frontiers in Bioengineering and Biotechnology, 2022)
The demand for non-petroleum-based, especially biodegradable plastics has been on the rise in the last decades. Medium-chain-length polyhydroxyalkanoate (mcl-PHA) is a biopolymer composed of 6–14 carbon atoms produced from renewable feedstocks and has become the focus of research. In recent years, researchers aimed to overcome the disadvantages of single strains, and artificial microbial consortia have been developed into efficient platforms. In this work, we reconstructed the previously developed microbial consortium composed of engineered Pseudomonas putida KT∆ABZF (p2-a-J) and Escherichia coli ∆4D (ACP-SCLAC). The maximum titer of mcl-PHA reached 3.98 g/L using 10 g/L glucose, 5 g/L octanoic acid as substrates by the engineered P. putida KT∆ABZF (p2-a-J). On the other hand, the maximum synthesis capacity of the engineered E. coli ∆4D (ACP-SCLAC) was enhanced to 3.38 g/L acetic acid and 0.67 g/L free fatty acids (FFAs) using 10 g/L xylose as substrate. Based on the concept of “nutrient supply-detoxification,” the engineered E. coli ∆4D (ACP-SCLAC) provided nutrient for the engineered P. putida KT∆ABZF (p2-a-J) and it acted to detoxify the substrates. Through this functional division and rational design of the metabolic pathways, the engineered P. putida-E. coli microbial consortium could produce 1.30 g/L of mcl-PHA from 10 g/L glucose and xylose. Finally, the consortium produced 1.02 g/L of mcl-PHA using lignocellulosic hydrolysate containing 10.50 g/L glucose and 10.21 g/L xylose as the substrate. The consortium developed in this study has good potential for mcl-PHA production and provides a valuable reference for the production of high-value biological products using inexpensive carbon sources.